Sodium ion battery negative electrode of carbon-coated carbon nanofiber and preparation method thereof

By using carbon-coated carbon nanofibers as the negative electrode material in sodium ion batteries, the problems of insufficient conductivity and cycle stability of the negative electrode material of sodium ion batteries are solved, and higher battery performance and longer cycle life are achieved.

CN119754020APending Publication Date: 2025-04-04QINGDAO FUSION EQUIP TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411671251.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The conductivity and cycle stability of the negative electrode material of sodium ion battery are poor, resulting in a degradation of battery performance.

Method used

Carbon-coated carbon nanofibers are used as the negative electrode material of sodium ion battery. The conductive skeleton and carbon shell of carbon nanofibers are combined to improve the conductivity and structural stability of the material.

Benefits of technology

It significantly improves the battery's conductivity and cycle stability, extends the battery's cycle life, and improves sodium storage capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119754020A_ABST
    Figure CN119754020A_ABST
Patent Text Reader

Abstract

The present invention discloses a sodium ion battery negative electrode of carbon-coated carbon nanofibers and a preparation method thereof, and belongs to the technical field of sodium ion batteries. The technical scheme is as follows: comprising the following steps: 1) Preparation of carbon nanofibers: dissolving polymer materials in organic solvents to form polymer solutions; spraying polymer solutions into polymer fibers; polymer fibers forming carbon nanofibers; 2) Composite carbon nanofibers with carbon materials: mixing carbon nanofibers with carbon precursors to make the carbon precursors evenly distributed on the surface of carbon nanofibers to form a mixed solution, placing the mixed solution in a hydrothermal reactor to undergo a hydrothermal reaction, and obtaining carbon nanofiber sheets; 3) cleaning and drying; 4) carbonization treatment, and finally obtaining carbon-coated carbon nanofibers. The present invention uses carbon nanofibers as a conductive skeleton, which not only provides a good electron transmission channel, but also enhances the structural stability of the material through carbon coating technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a carbon-coated carbon nanofiber sodium ion battery negative electrode and a preparation method thereof. Background Art

[0002] With the growing demand for clean energy, lithium-ion batteries occupy an important position in the field of energy storage due to their high energy density and long cycle life. However, the limited lithium resources are becoming a bottleneck restricting their large-scale application. Therefore, finding alternative and resource-rich energy storage solutions has become a hot topic in current research. As a potential alternative, sodium-ion batteries have attracted much attention due to the abundance and low cost of sodium resources. However, sodium-ion batteries still face many challenges in terms of energy density and cycle life, especially the performance of negative electrode materials has become the key to restricting their development. Carbon materials, as a widely used negative electrode material in lithium-ion batteries, are also increasingly studied in sodium-ion batteries. However, due to the large volume of sodium ions, carbon materials are prone to volume changes during charging and discharging, resulting in a decrease in battery performance. Therefore, the development of sodium-ion battery negative electrode materials with excellent stability and conductivity has become the key to promoting the development of sodium-ion battery technology.

[0003] However, in the research and development of sodium-ion batteries, the selection and preparation of negative electrode materials has become an important problem. Graphite, the traditional negative electrode material of lithium batteries, cannot effectively accommodate sodium ions with a larger radius due to its small interlayer spacing, which limits its application in sodium-ion batteries. At present, the mainstream negative electrode materials for sodium-ion batteries on the market are mainly concentrated in soft carbon and hard carbon. Although these two materials have a certain sodium storage capacity, their conductivity and cycle stability are relatively poor. Therefore, it is necessary to develop a sodium-ion battery negative electrode material with high conductivity and cycle stability. Summary of the invention

[0004] The present invention provides a carbon-coated carbon nanofiber sodium ion battery negative electrode and a preparation method thereof. The carbon nanofiber is used as a conductive skeleton, which not only provides a good electron transmission channel, but also enhances the structural stability of the material through the carbon coating technology. At the same time, the introduction of the carbon shell optimizes the embedding and extraction behavior of sodium ions during the charging and discharging process, and improves the sodium storage capacity and cycle life of the material.

[0005] The technical solution of the present invention is:

[0006] In a first aspect, a method for preparing a negative electrode of a sodium ion battery of carbon-coated carbon nanofibers is disclosed, comprising the following steps:

[0007] 1) Preparation of carbon nanofibers: dissolving a polymer material in an organic solvent to form a polymer solution; spraying the polymer solution into polymer fibers by electrostatic spinning; pre-oxidizing the polymer fibers to form nanofibers, and then carbonizing them at high temperature to form carbon nanofibers;

[0008] 2) Composite carbon nanofibers and carbon materials: firstly treat the carbon precursor, then mix the carbon nanofibers with the carbon precursor, make the carbon precursor evenly distributed on the surface of the carbon nanofibers to form a mixed liquid, place the mixed liquid in a hydrothermal reactor to undergo a hydrothermal reaction, and obtain a carbon nanofiber sheet;

[0009] 3) Cleaning and drying: Clean the carbon nanofiber sheet to remove the attached matter on the surface and dry it;

[0010] 4) Carbonization treatment: placing the dried carbon nanofiber sheet in an inert atmosphere for carbonization treatment to finally obtain carbon-coated carbon nanofibers;

[0011] Preferably, the carbon precursor includes a hard carbon precursor and a soft carbon precursor; when the precursor is a hard carbon precursor, the pretreatment is to crush and screen the hard carbon precursor; when the precursor is a soft carbon precursor, the pretreatment is to place the soft carbon precursor in air for calcination pre-oxidation treatment.

[0012] Preferably, in step 2), the hydrothermal reaction temperature is 120-200° C., and the reaction time is 6-12 h.

[0013] Preferably, in step 1), the polymer material is one of polyvinyl pyrrolidone and polyacrylic acid, and the organic solvent is one of dimethylformamide, dimethyl sulfoxide, dimethylacetamide and ethyl acetate.

[0014] Preferably, the polymer solution is formed in step 1) by stirring at 25-50° C. for 4-24 hours.

[0015] Preferably, in step 1), the pre-oxidation temperature is 100-200° C., the pre-oxidation time is 6-12 h, the high-temperature carbonization temperature is 800-1000° C., and the carbonization time is 2-6 h.

[0016] Preferably, when the precursor is a hard carbon precursor, the pretreatment is to crush the hard carbon precursor and select a 50-150 mesh sieve for screening; when the precursor is a soft carbon precursor, the pretreatment is to first place the soft carbon precursor in the air for calcination pre-oxidation treatment, the calcination pre-oxidation treatment temperature is 100-300°C, the time is 6-12h, and the pre-oxidized soft carbon precursor is crushed and selected a 50-150 mesh sieve for screening.

[0017] Preferably, in step 2), the carbon nanofibers and the carbon precursor are mixed by ultrasound for a mixing time of 0.5-2 h.

[0018] Preferably, in step 4), the inert atmosphere is argon or nitrogen atmosphere, the carbonization temperature is 750-850° C., and the carbonization time is 1-8 h.

[0019] In a second aspect, a sodium ion battery negative electrode material of carbon-coated carbon nanofibers prepared by the preparation method is disclosed.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1. In terms of conductivity, the conductive skeleton composed of carbon nanofibers significantly improves the overall conductivity of the negative electrode material. This not only speeds up the electron transmission speed inside the battery, but also improves the battery's charge and discharge efficiency, providing a strong guarantee for the high-performance operation of sodium-ion batteries.

[0022] 2. In terms of cycle stability, the introduction of carbon coating technology significantly enhances the structural stability of the negative electrode material. The carbon shell formed by carbon coating effectively prevents the structural damage and pulverization of the material during the charge and discharge process, thereby extending the cycle life of the battery. The experimental results show that the hard carbon negative electrode material prepared by the present invention can still maintain good electrochemical properties after multiple charge and discharge cycles, showing excellent cycle stability. After 150 cycles at 0.1C, the capacity is still stable at about 290mAh / g. After 500 cycles at 1C, the capacity is stable at about 250mAh / g. The material has good cycle stability at high rates.

[0023] 3. In terms of sodium storage capacity, carbon-coated carbon nanofiber negative electrode materials also show obvious advantages. By optimizing the embedding and extraction behavior of sodium ions during the charging and discharging process, the sodium storage capacity of the material has been effectively improved, and the discharge capacity of the first cycle can reach 440mAh / g. This not only improves the energy density of the battery, but also enhances the practicality of the battery, allowing sodium-ion batteries to be used in more fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a scanning electron microscope image of the hard carbon-coated carbon nanofibers obtained in Example 1 of the present invention.

[0025] Figure 2 3 is the XRD diagram of the hard carbon-coated carbon nanofibers obtained in Example 1 of the present invention.

[0026] Figure 3 This is a graph showing changes in the first three cycles of a battery assembled using the hard carbon-coated carbon nanofibers prepared in Example 1 as the negative electrode material.

[0027] Figure 4 The figure is the cycle performance at a rate of 0.1C of a battery assembled using the hard carbon-coated carbon nanofibers prepared in Example 1 as the negative electrode material.

[0028] Figure 5 This is a cycle test chart of a battery assembled using the hard carbon-coated carbon nanofibers prepared in Example 1 as the negative electrode material at a 1C rate.

[0029] Figure 6 3 is the XRD diagram of the soft carbon-coated carbon nanofibers obtained in Example 2 of the present invention.

[0030] Figure 7 This is a cycle test chart of a battery assembled using the soft carbon-coated carbon nanofibers prepared in Example 2 as the negative electrode material at a 1C rate. DETAILED DESCRIPTION

[0031] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.

[0032] Example 1

[0033] This embodiment provides a method for preparing a sodium ion battery negative electrode of hard carbon coated carbon nanofibers, comprising the following steps:

[0034] 1) Preparation of carbon nanofibers:

[0035] a. Preparation of spinning solution: 1 g of polyvinyl pyrrolidone (PVP) powder was added to 10 mL of dimethylformamide (DMF). The mixture was then stirred at 50° C. for 24 h using a stirrer to ensure that PVP was completely dissolved in DMF to form a uniform spinning solution.

[0036] b. Preparation of nanofibers: Nanofibers are prepared using an electrospinning machine. The prepared spinning solution is injected into the electrospinning machine, and the propulsion speed is set to 0.1 mm / min, the positive pressure is 18 kV, and the negative pressure is -2 kV. Under the action of the electrostatic field, the spinning solution is stretched into nanofibers and collected on the receiving plate. In order to enhance the stability of the nanofibers, we perform a pre-oxidation treatment. The collected nanofibers are placed in a pre-oxidation furnace and pre-oxidized in air at a preset temperature of 200°C for 12 hours. The pre-oxidation process helps to stabilize the internal structure of the nanofibers and prepare for subsequent carbonization treatment.

[0037] c. Preparation of carbon nanofibers: The pre-oxidized nanofibers were placed in a tubular furnace and subjected to high-temperature carbonization treatment under an argon atmosphere. The carbonization temperature was set at 800°C and the carbonization time was set at 3 hours. During the carbonization process, the organic components in the nanofibers were gradually converted into carbon, and carbon nanofibers were finally obtained.

[0038] 2) Carbon nanofiber and carbon material composite:

[0039] d. Treatment of hard carbon precursor: Select discarded dry soybean meal as a hard carbon precursor. Use a pulverizer to crush the dry soybean meal into fine particles, and then use a 100-mesh sieve to sieve the soybean meal powder to obtain a powder with uniform particle size. Take 0.5g of the sieved soybean meal powder, dissolve it in 20mL of distilled water, and stir it to form a uniform suspension. Then, put a piece of carbon nanofiber with a specification of 40×20mm into the suspension, ensuring that the fiber is completely immersed in the soybean meal suspension.

[0040] e. Preparation of carbon nanofiber sheets: Place the mixed system containing carbon nanofibers and soybean meal suspension into an ultrasonic machine and perform ultrasonic treatment for 0.5 hours. Ultrasonic treatment helps the soybean meal powder to adhere more evenly to the surface of the carbon nanofibers. Place the ultrasonically treated solution and the carbon nanofibers into a reactor for hydrothermal reaction. Set the reaction temperature to 150°C and the reaction time to 12 hours. During the hydrothermal reaction, the soybean meal powder is transformed on the surface of the carbon nanofibers to form a preliminary hard carbon coating layer, thus obtaining a carbon nanofiber sheet.

[0041] 3) Cleaning and drying:

[0042] After the reaction is completed, the carbon nanofiber sheet is taken out and repeatedly rinsed with distilled water and ethanol to remove the unreacted soybean meal powder and impurities attached to the surface. This step is crucial to ensure the purity of the final product. The washed carbon nanofiber sheet is placed in a vacuum oven for drying. The drying temperature is 120°C and the drying time is 24 hours to ensure that the moisture in the fiber is completely evaporated to obtain a dry hard carbon-coated carbon nanofiber sheet.

[0043] 4) Carbonization treatment: The dried hard carbon-coated carbon nanofiber sheet is placed in a tubular furnace for high-temperature carbonization treatment. Under an argon atmosphere, the carbonization temperature is set to 800°C and the carbonization time is 3 hours. During the carbonization process, the soybean meal powder is completely converted into a hard carbon material and is tightly combined with the carbon nanofiber to form a stable hard carbon coating layer, that is, hard carbon-coated carbon nanofibers are obtained.

[0044] The scanning electron microscope image of the hard carbon-coated carbon nanofibers obtained in this example is as follows: Figure 1 shown. Figure 1It shows a network composed of many fibrous structures, which are carbon nanofibers. They are interlaced in space to form a three-dimensional interconnected structure; the surface of the carbon nanofibers is covered with a layer of granular material, which is a hard carbon coating. This coating is prepared by hydrothermal reaction to improve the electrochemical performance of the material; the scale of the image shows that the diameter of the carbon nanofibers is about 600 nanometers, which is in line with the typical size of carbon nanofibers; this fibrous network structure helps to improve conductivity, because carbon nanofibers themselves have good conductivity, and the coated carbon layer can further improve this property; the porous structure is conducive to the embedding and extraction of sodium ions, which may help to improve the capacity and cycle stability of sodium batteries; the carbon coating on the surface can not only prevent the volume expansion of the fiber during charging and discharging, but also enhance the chemical stability of the material, thereby extending the life of the battery.

[0045] The XRD pattern of the hard carbon-coated carbon nanofibers obtained in this example is as follows: Figure 2 As shown, there is a strong diffraction peak at about 2θ=26: This usually corresponds to the diffraction peak of the (002) plane of graphitized carbon materials. For hard carbon materials, this peak is usually wider, indicating that the material has a higher degree of disorder and a larger interlayer spacing, and does not have a distinct crystal structure like highly graphitized carbon. A small peak near 2θ=43: This usually corresponds to the diffraction peak of the (100) plane, reflecting a small amount of ordered graphitized structure in the material, but due to the lower intensity, it indicates a low degree of graphitization. The disordered structure of hard carbon can provide more active sites for the embedding and extraction of sodium ions, which is beneficial to improving the sodium storage performance of the battery. The larger interlayer spacing of hard carbon is suitable for the embedding of sodium ions, which improves the sodium storage capacity of the material.

[0046] Example 2

[0047] This embodiment provides a method for preparing a sodium ion battery negative electrode of soft carbon-coated carbon nanofibers, comprising the following steps:

[0048] 1) Preparation of spinning solution:

[0049] a. Add 1 g of polyvinyl pyrrolidone (PVP) powder to 10 mL of dimethylformamide (DMF). Then, use a stirrer to continuously stir the mixture at 50°C for 24 h to ensure that the PVP is completely dissolved in DMF to form a uniform spinning solution.

[0050] b. Preparation of nanofibers: Nanofibers are prepared using an electrospinning machine. The prepared spinning solution is injected into the electrospinning machine, and the propulsion speed is set to 0.1 mm / min, the positive pressure is 18 kV, and the negative pressure is -2 kV. Under the action of the electrostatic field, the spinning solution is stretched into nanofibers and collected on the receiving plate. In order to enhance the stability of the nanofibers, the collected nanofibers are placed in a pre-oxidation furnace and pre-oxidized in air at a preset temperature of 200°C for 12 hours. The pre-oxidation process helps to stabilize the internal structure of the nanofibers and prepare for subsequent carbonization treatment.

[0051] c. Preparation of carbon nanofibers: The pre-oxidized nanofibers were placed in a tubular furnace and subjected to high-temperature carbonization treatment under an argon atmosphere. The carbonization temperature was set at 800°C and the carbonization time was set at 3 hours. During the carbonization process, the organic components in the nanofibers were gradually converted into carbon, and carbon nanofibers were finally obtained.

[0052] 2) Carbon nanofiber and carbon material composite:

[0053] d. Treatment of soft carbon precursor: 0.5 g of glucose powder was pre-oxidized in air at 180°C for 6 hours to initially form a hardened mesophase material. Subsequently, the pre-oxidized glucose powder was dissolved in 20 ml of distilled water and stirred to form a uniform suspension.

[0054] e. Preparation of carbon nanofiber sheets:

[0055] A carbon nanofiber sheet with a size of 40×20 mm was placed in a glucose suspension to ensure that the fiber was completely impregnated. The mixed system was then placed in an ultrasonic machine for 0.5 hours of ultrasonic treatment to ensure that the soft carbon precursor was evenly attached to the surface of the carbon nanofiber. The treated mixed system was transferred to a hydrothermal reactor and subjected to a hydrothermal reaction at 150°C for 12 hours. During the hydrothermal reaction, glucose was converted on the surface of the carbon nanofiber to form a preliminary soft carbon coating layer, thus obtaining a soft carbon-coated carbon nanofiber sheet.

[0056] 3) Cleaning and drying:

[0057] After the reaction is completed, the carbon nanofiber sheet is taken out and repeatedly rinsed with distilled water and ethanol to remove the unreacted residual substances attached to the surface. The washed carbon nanofiber sheet is placed in a vacuum oven for drying. The drying temperature is 80°C and the drying time is 12 hours to ensure that the fiber is completely dry.

[0058] 4) Carbonization treatment:

[0059] The dried soft carbon-coated carbon nanofiber sheet was placed in a tubular furnace for high-temperature carbonization. Under an argon atmosphere, the carbonization temperature was set at 800°C and the carbonization time was 3 hours. During the carbonization process, the glucose precursor was completely converted into a soft carbon material and tightly combined with the carbon nanofibers, eventually forming a stable soft carbon coating layer to obtain soft carbon-coated carbon nanofibers.

[0060] The XRD pattern of the soft carbon-coated carbon nanofibers obtained in this example is as follows: Figure 6 As shown, analysis shows that its crystallinity is low and the degree of graphitization is insufficient. A wider (002) diffraction peak is observed at 2θ≈26°, indicating that the layered structure of the material has a high degree of disorder. The wider diffraction peak indicates that the material lacks regular stacking of carbon layers, and the interlayer spacing is relatively large, forming a looser disordered structure. In addition, the (100) diffraction peak at 2θ≈43° is weaker, further indicating that there are fewer ordered graphitized areas in the material. Compared with the hard carbon material of Example 1, the low graphitization characteristics of this material make its conductivity and structural stability inferior to hard carbon. Hard carbon materials can generally form a denser carbon layer structure under high-temperature carbonization conditions, providing higher conductivity and cycle stability. However, the material in Comparative Example 2 has loose carbon layer stacking, discontinuous electron conduction paths, and low electrical conductivity due to low-temperature treatment, and thus exhibits poor performance in battery applications.

[0061] Nevertheless, the disordered carbon structure of this material still has certain advantages. The larger interlayer spacing provides more embedding sites for sodium ions, which promotes the embedding and extraction of sodium ions, especially during the initial charge and discharge process, showing a higher sodium ion storage capacity. At the same time, although the structural stability is not as good as hard carbon, its porous and disordered carbon structure can buffer the volume expansion to a certain extent and maintain the basic structure of the electrode.

[0062] Comparative Example 1

[0063] Different from Example 1, in step 1) of this comparative example, "1g polyvinyl pyrrolidone (PVP)" is replaced with "1g polyacrylonitrile (PAN)", and the remaining preparation steps are the same as Example 1. PVP has low viscosity and good rheological properties, is suitable for electrospinning process, and the fibers formed during spinning are more uniform and stable; while PAN, due to its high molecular weight and viscosity, is easy to form a coarser fiber structure, resulting in excessively coarse and uneven fiber diameter; PVP forms a disordered but open carbon structure during carbonization, which has a large surface area and is suitable for ion embedding and extraction; while PAN, when carbonized at high temperature, forms a denser graphitized carbon material, lacks a porous structure, has relatively low conductivity, and has a reduced surface area, which is not conducive to the embedding and extraction of sodium ions.

[0064] Comparative Example 2

[0065] Unlike Example 1, in step 1) of this comparative example, "10 mL of dimethylformamide (DMF)" is replaced with "10 mL of methanol", and the remaining preparation steps are the same as in Example 1. DMF is a highly polar solvent that can dissolve PVP well and form a viscous, uniform spinning solution. In contrast, methanol has a lower polarity, and its molecular structure is not suitable for fully dissolving PVP, which deteriorates the viscosity and uniformity of the spinning solution and affects the fiber forming effect; DMF evaporates slowly, which is beneficial to the stretching and forming of the fiber during the spinning process; the evaporation rate of methanol is too fast, which may cause the solution to dry prematurely at the nozzle, resulting in insufficient fiber stretching, fiber breakage or irregular fiber structure. This will have an adverse effect on the uniformity and performance of the fiber; the electrospinning process depends on the uniformity and rheological properties of the solution. Using DMF can obtain uniform, uniform diameter nanofibers, which helps to form a larger specific surface area and a good conductive path. The carbon fiber structure formed after methanol substitution is prone to voids, breaks or larger pores, making it difficult to form an effective electron transport network, thereby affecting the electrochemical performance of the battery.

[0066] Comparative Example 3

[0067] Unlike Example 1, this comparative example does not include the pre-oxidation treatment in step 1). Pre-oxidation is an important process for preparing carbon nanofiber membranes by electrospinning, and is an important process for converting polymer materials into carbon materials. The purpose is to increase the mechanical strength and thermal stability of the fiber so that it can be used under high temperature and high strength conditions. Pre-oxidation can partially oxidize elements such as hydrogen, oxygen and nitrogen in the polymer fiber, and a series of complex reactions such as cyclization, cross-linking, dehydrogenation, oxidation, etc. of the molecular chain occur, so that it is converted into a thermally stable pyridine ring ladder structure with a semiconductor resistance value, and its heat resistance, flame retardancy and conductivity are all improved, reducing the internal stress and thermal shrinkage of the fiber during the carbonization process of the fiber, and improving the carbonization efficiency. If direct carbonization is adopted to prepare carbon nanofibers, the flexibility of the carbon nanofibers will be lost. When assembling the battery, the electrode material will be subjected to mechanical stress, resulting in the breakage of the self-supporting electrode. The broken electrode will increase the contact area with the electrolyte, and the process of generating SEI during the first charge and discharge process will consume more active sodium, and the first coulomb efficiency and reversible capacity will both decrease.

[0068] Comparative Example 4

[0069] Unlike Example 1, the carbonization temperature in step c of step 1) is 700°C, and the remaining steps and methods are the same as in Example 1. When the carbonization temperature is low, the ordered structure and degree of graphitization inside the carbon material are insufficient, and the arrangement of carbon atoms is relatively disordered, which limits the electrical conductivity of the material. 800°C is the critical temperature for achieving higher electrical conductivity of carbon materials, while 700°C cannot achieve this effect. High-temperature carbonization helps cross-linking and densification of carbon chains, giving carbon nanofibers stronger mechanical stability and durability. 700°C cannot completely remove organic residues, which reduces the strength and durability of carbon materials, resulting in structural instability during repeated charge and discharge. The electrical conductivity and structural integrity of carbon nanofibers are crucial to the cycle performance of the battery. The carbonization temperature of 700°C is not enough to form a high-quality conductive skeleton and a stable carbon structure. The electrode structure is easily damaged during the charge and discharge process, resulting in a decrease in the conduction and storage efficiency of sodium ions.

[0070] Comparative Example 5

[0071] Different from Example 1, a 40-mesh screen is used to screen the soybean meal powder in step d of step 2), and the remaining steps and methods are the same as those in Example 1. The fine-mesh screen used in Example 1 helps to obtain powder with smaller and more uniform particle size, which can be more evenly attached to the surface of the carbon nanofiber; while the larger particles obtained by the 100-mesh screen are difficult to evenly cover the fiber surface, and the coating layer may appear uneven in thickness, affecting the structural integrity of the material. Small and uniform particles are more likely to fit on the surface of carbon nanofibers and form a dense carbon coating layer, while large particles are prone to cracks or gaps due to uneven volume shrinkage during the carbonization process. This unstable coating may become pulverized during repeated charge and discharge, resulting in rapid degradation of the performance of the electrode material.

[0072] Comparative Example 6

[0073] Different from Example 1, in step e) of step 2), ultrasonic treatment is not used but ordinary stirring is used for 0.5h, and the remaining steps and methods are the same as those of Example 1. Ultrasonic treatment utilizes the bursting effect of tiny bubbles generated by sound waves to fully disperse the precursor particles in the suspension and evenly adhere to the surface of carbon nanofibers; while ordinary stirring cannot provide such high-energy dispersion effect, and it is easy to form particle aggregation, resulting in uneven thickness of the carbon coating layer, which affects the electrochemical properties of the negative electrode material. Ultrasonic treatment can make the precursor particles fit closely to the fiber surface to form a dense coating layer, while the stirring effect is weak, and it is difficult to achieve such a close adhesion effect, which may cause the coating layer to shrink unevenly or fall off during carbonization.

[0074] Comparative Example 7

[0075] Different from Example 1, the carbonization temperature in step 4) is 700°C, and the remaining steps and methods are the same as in Example 1. During the carbonization process, a higher temperature (such as 800°C) helps to form a more ordered carbon structure, thereby improving the conductivity of the material. The carbonization temperature of 700°C may not provide enough energy to promote the transformation of the disordered carbon chain structure to order, resulting in poor conductivity of the carbon layer, affecting the overall performance of the battery. The carbonization temperature of 800°C helps to densify the hard carbon layer, so that the material has higher mechanical strength and structural integrity. However, when carbonized at 700°C, the carbon structure may not be dense enough, and there are more pores or microcracks in the formed hard carbon layer, which makes the material easy to degrade or pulverize in repeated cycles.

[0076] Comparative Example 8

[0077] Different from Example 1, the carbonization temperature in step 4) is 900°C, and the remaining steps and methods are the same as in Example 1. During carbonization at high temperatures (such as 900°C), the arrangement of carbon atoms tends to be more orderly, forming a carbon structure with a higher degree of graphitization. This structure has better conductivity, but it is also more brittle and not easy to adapt to the volume changes caused by the insertion and extraction of sodium ions, thereby affecting the long-term stability of the electrode material. At a high temperature of 900°C, the structure of the carbon material tends to graphitize and the interlayer spacing becomes smaller. This smaller interlayer spacing limits the embedding channel of sodium ions, reduces the specific capacity of the material, and is not conducive to achieving efficient sodium ion storage.

[0078] The negative electrode material prepared in Example 1-2 is cut to prepare the shape and size of the negative electrode sheet of the battery, and it is assembled into the battery structure to perform the battery performance test. It should be noted that in addition to the negative electrode sheet, the other materials required for assembling the battery are common materials available on the market, and are assembled using conventional methods in the field. This test assembles a button half-battery, which is divided into a working electrode and a counter electrode. The working electrode is the negative electrode material prepared in Example 1-2 as an electrode, and the counter electrode is a sodium metal sheet. The assembly method of the button battery is as follows: first, a sodium metal sheet is added to the negative electrode shell to ensure good contact with the negative electrode shell. Then place a diaphragm to prevent the working electrode from short-circuiting with the sodium metal sheet, and then drip an appropriate amount of electrolyte on the diaphragm to ensure the conductivity inside the battery. Subsequently, the working electrode sheet prepared by the negative electrode material prepared in Example 1-2 is placed on the diaphragm to ensure good contact. Then place the gasket and the shrapnel in turn to enhance the mechanical stability of the battery and ensure that the internal components are tightly connected. Finally, buckle the positive electrode shell to ensure alignment, and use a packaging machine to tightly seal the battery to prevent leakage of the electrolyte. After completing these steps, the coin cell is ready for use or subsequent testing.

[0079] The changes in the first three cycles of the battery assembled using the hard carbon-coated carbon nanofibers prepared in Example 1 as the negative electrode material are as follows: Figure 3As shown in the figure, it can be seen that the discharge platform of the first cycle is low, and the voltage drops rapidly from about 2.5V to nearly 0.1V. This is usually related to the irreversible reaction of sodium ions when they are first embedded in the negative electrode material, such as electrolyte decomposition, formation of solid electrolyte interface (SEI) film, etc. This process usually leads to a high initial irreversible capacity loss. The discharge capacity of the first cycle is about 440mAh / g, which is relatively high among the negative electrode materials of sodium ion batteries, indicating that the material has a large sodium ion storage capacity. From the second cycle, the charge and discharge curves tend to be stable, and the discharge platform is raised to about 0.5V-0.6V. This shows that after the first cycle, a relatively stable SEI film is formed on the surface of the material, reducing the loss of irreversible capacity. The shape and position of the discharge curve do not change much, which shows that the material has good cycle stability in the subsequent charge and discharge process. The curves of the third cycle and the second cycle are almost coincident, indicating that after the initial cycle, the capacity decay of the material is very small, showing good cycle stability.

[0080] The cycle performance of the battery assembled using the hard carbon-coated carbon nanofibers prepared in Example 1 as the negative electrode material at a rate of 0.1C is as follows: Figure 4 As shown in the figure, at a rate of 0.1C, the prepared hard carbon-coated carbon nanofiber material exhibits excellent cycling performance. It can be observed from the cycling performance diagram that the material exhibits a high specific capacity of about 430 mAh / g at the initial discharge. This high capacity decreases slightly within the first 20 cycles, then stabilizes and remains at about 340 mAh / g in the following cycles. The entire test process is close to 150 cycles, and after a long cycle, the capacity remains stable at about 290 mAh / g, indicating that the material has good cycling stability and a slow capacity decay rate. The high initial capacity and high capacity retention rate after long cycles indicate that the material can effectively maintain its structural stability during multiple charge and discharge cycles without significant structural collapse or failure. This stable cycling performance is very beneficial for the practical application of sodium-ion batteries because it means that the material can maintain a high sodium storage capacity during long-term use, thereby extending the service life of the battery.

[0081] The cycle test diagram of the battery assembled using the hard carbon-coated carbon nanofibers prepared in Example 1 as the negative electrode material at 1C rate is as follows Figure 5As shown in the figure, in the cycle performance test at 1C rate, the hard carbon-coated carbon nanofiber material showed good electrochemical stability and high discharge capacity; at 1C rate, the initial discharge capacity of the material was 260mAh / g. This is a relatively high initial capacity, indicating that the material can still effectively embed and extract sodium ions at high rates, and has good specific capacity performance; the capacity is stable at about 250mAh / g during the entire 500-cycle test. In the subsequent cycles, the discharge capacity remained basically stable, indicating that the material has excellent cycle performance; even after 500 cycles of long-term cycling, the capacity of the material still remains at a relatively high level, indicating that the material has good cycle stability at high rates; at a high charge and discharge rate of 1C, the material can maintain a stable capacity, indicating that its structure has not undergone significant degradation in high-rate cycles. This performance is critical for the rapid charging and discharging requirements in practical applications, especially in fields such as electric vehicles that require high-rate rapid charging and discharging; the stable performance at high rates shows that the material has good electronic conductivity and ionic conductivity, and can quickly handle changes in current density while maintaining structural integrity.

[0082] The cycle test diagram of the battery assembled using the soft carbon-coated carbon nanofibers prepared in Example 2 as the negative electrode material at 1C rate is shown in the figure Figure 7 As shown, after five cycles of 0.1C activation, the initial discharge specific capacity is 405mAh / g. In the subsequent cycles, the 1C rate test was used, and the capacity tended to stabilize in the subsequent cycles, maintaining at about 300mAh / g. After 200 cycles of testing, the capacity stabilized at about 230mAh / g, which shows that the material has a certain stability during the cycle. It can be seen from the data that the material of Example 2 still maintains basic structural integrity after multiple charge and discharge cycles. Although the present invention is described in detail in conjunction with the preferred embodiments, the present invention is not limited thereto. Without departing from the spirit and essence of the present invention, a person of ordinary skill in the art may make various equivalent modifications or substitutions to the embodiments of the present invention, and these modifications or substitutions should be within the scope of the present invention. Therefore, the scope of protection of the present invention shall be based on the scope of protection of the claims.

Claims

1. A method for preparing a negative electrode for a sodium ion battery of carbon-coated carbon nanofibers, characterized in that: The following steps are involved: 1) Preparation of carbon nanofibers: dissolving a polymer material in an organic solvent to form a polymer solution; spraying the polymer solution into polymer fibers by electrostatic spinning; pre-oxidizing the polymer fibers to form nanofibers, and then carbonizing them at high temperature to form carbon nanofibers; 2) Composite carbon nanofibers and carbon materials: firstly treat the carbon precursor, then mix the carbon nanofibers with the carbon precursor, make the carbon precursor evenly distributed on the surface of the carbon nanofibers to form a mixed liquid, place the mixed liquid in a hydrothermal reactor to undergo a hydrothermal reaction, and obtain a carbon nanofiber sheet; 3) Cleaning and drying: Clean the carbon nanofiber sheet to remove the attached matter on the surface and dry it; 4) Carbonization treatment: The dried carbon nanofiber sheet is placed in an inert atmosphere for carbonization treatment to finally obtain carbon-coated carbon nanofibers.

2. The method for preparing a negative electrode for a sodium ion battery of carbon-coated carbon nanofibers according to claim 1, characterized in that: The carbon precursor includes a hard carbon precursor and a soft carbon precursor; when the precursor is a hard carbon precursor, the pretreatment is to crush and screen the hard carbon precursor; when the precursor is a soft carbon precursor, the pretreatment is to place the soft carbon precursor in the air for calcination pre-oxidation treatment.

3. The method for preparing a negative electrode for a sodium ion battery of carbon-coated carbon nanofibers according to claim 1, characterized in that: In step 2), the hydrothermal reaction temperature is 120-200° C. and the reaction time is 6-12 h.

4. The method for preparing a negative electrode for a sodium ion battery of carbon-coated carbon nanofibers according to claim 1, characterized in that: In step 1), the polymer material is one of polyvinyl pyrrolidone and polyacrylic acid, and the organic solvent is one of dimethylformamide, dimethyl sulfoxide, dimethylacetamide and ethyl acetate.

5. The method for preparing a negative electrode for a sodium ion battery of carbon-coated carbon nanofibers according to claim 1, characterized in that: In step 1), the polymer solution is formed by stirring at 25-50° C. for 4-24 hours.

6. The method for preparing a negative electrode for a sodium ion battery of carbon-coated carbon nanofibers according to claim 1, characterized in that: In step 1), the pre-oxidation temperature is 100-200° C., the pre-oxidation time is 6-12 hours, the high-temperature carbonization temperature is 800-1000° C., and the carbonization time is 2-6 hours.

7. The method for preparing a negative electrode for a sodium ion battery of carbon-coated carbon nanofibers according to claim 2, characterized in that: When the precursor is a hard carbon precursor, the pretreatment is to crush the hard carbon precursor and select a 50-150 mesh sieve for screening; when the precursor is a soft carbon precursor, the pretreatment is to first place the soft carbon precursor in the air for calcination pre-oxidation treatment, the calcination pre-oxidation temperature is 100-300 ° C, the time is 6-12h, and the pre-oxidized soft carbon precursor is crushed and selected a 50-150 mesh sieve for screening.

8. The method for preparing a negative electrode for a sodium ion battery of carbon-coated carbon nanofibers according to claim 1, characterized in that: In step 2), the carbon nanofibers and the carbon precursor are mixed by ultrasound, and the mixing time is 0.5-2h.

9. The method for preparing a negative electrode for a sodium ion battery of carbon-coated carbon nanofibers according to claim 1, characterized in that: In step 4), the inert atmosphere is argon or nitrogen, the carbonization temperature is 750-850° C., and the carbonization time is 1-8 hours.

10. A sodium ion battery negative electrode material of carbon-coated carbon nanofibers prepared by the preparation method according to any one of claims 1 to 9.